A new Megatheriinae skull (Xenarthra, Tardigrada) from the pliocene of northern venezuela – Implications for a giant sloth dispersal to central and North America - Carlini, Alfredo Armando (2018)
A skull of a ground sloth from the Pliocene San Gregorio Formation documents a northern neotropical occurrence of a megatheriine that addresses issues on intraspecific variation and biogeography. The new specimen is broadly similar in size and morphology to that of Proeremotherium eljebe from the underlying Codore Formation in the Urumaco Sequence, differing in several features such as a longer basicranial area and a more posteriorly projected basioccipital between the condyles. The living sloths species of Bradypus and Choloepus do not have unequivocal anatomical features that indicate sexual dimorphism. Nevertheless, fossil sloths may have shown such dimorphism, and speculations on this subject are part of the considerations that can be made when allocating fragmentary fossils (e.g., in the new skull the presence of a long sagittal crest could indicate a male individual and the absence of an extended crest in Proeremotherium eljebe a female one). We speculate that as early as the late middle Miocene, two main lines of Megatheriinae had clearly separated in two geographic areas, one in the rising Andean area and one at low latitudes on the lowlands of central and northern South America.